Towards doubling fibre yield for cotton in the semiarid agricultural area by increasing tolerance to drought, heat and salinity simultaneously - Esmaeili, Nardana (Plant Biotechnol J, 2020)
Abiotic stresses such as extreme temperatures, water‐deficit and salinity negatively affect plant growth and development, and cause significant yield losses. It was previously shown that co‐overexpression of the Arabidopsis vacuolar pyrophosphatase gene AVP1 and the rice SUMO E3 ligase gene OsSIZ1 in Arabidopsis significantly increased tolerance to multiple abiotic stresses and led to increased seed yield for plants grown under single or multiple abiotic stress conditions. It was hypothesized that there might be synergistic effects between AVP1 overexpression and OsSIZ1 overexpression, which could lead to substantially increased yields if these two genes are co‐overexpressed in real crops. To test this hypothesis, AVP1 and OsSIZ1 were co‐overexpressed in cotton, and the impact of OsSIZ1/AVP1 co‐overexpression on cotton's performance under normal growth and multiple stress conditions were analysed. It was found that OsSIZ1/AVP1 co‐overexpressing plants performed significantly better than AVP1‐overexpressing, OsSIZ1‐overexpressing and wild‐type cotton plants under single, as well as under multiple stress conditions in laboratory and field conditions. Two field studies showed that OsSIZ1/AVP1 co‐overexpressing plants produced 133% and 81% more fibre than wild‐type cotton in the dryland conditions of West Texas. This research illustrates that co‐overexpression of AVP1 and OsSIZ1 is a viable strategy for engineering abiotic stress‐tolerant crops and could substantially improve crop yields in low input or marginal environments, providing a solution for food security for countries in arid and semiarid regions of the world.